AI Tools for Academic Integrity: A Student Response to Chat GPT and Jenni AI in Citation Accuracy - Fitra Aulia Simatupang; Indi Azizah Nailah; Rita Hartati (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
This study investigates the role of Artificial Intelligence (AI) tools, specifically ChatGPT and Jenni AI, in supporting academic integrity through accurate citation generation. Employing a descriptive qualitative method, the research involved 30 undergraduate students who evaluated AI-generated citations using Fishman’s (2014) Academic Integrity Theory and Smith’s (2020) Citation Accuracy Framework. Data were collected through questionnaires assessing students’ perceptions of reliability, ethical responsibility, and accuracy in AI-assisted citation practices. Quantitative analysis revealed that Honesty and Accountability were the most dominant values (22.58% each), followed by Fairness and Respect (19.35% each), Trust (12.90%), and Courage (3.23%). Qualitative findings showed that students recognized AI’s potential to enhance writing efficiency but emphasized the need for human verification to ensure factual correctness and ethical compliance. Comparatively, Jenni AI demonstrated greater consistency and citation verification than ChatGPT, which exhibited more frequent fabrication and inaccuracy. The study concludes that while AI tools can enhance academic productivity, maintaining academic integrity still requires critical human oversight, ethical awareness, and adherence to scholarly honesty and accountability.